2013
DOI: 10.1016/j.cryobiol.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bovine serum albumin and fetal calf serum on sperm quality, DNA fragmentation and lipid peroxidation of the liquid stored rabbit semen

Abstract: The aim of the present study was to determine the effects of the bovine serum albumin (BSA) and fetal calf serum (FCS) on sperm quality, DNA fragmentation and lipid peroxidation of liquid stored rabbit semen stored up to 72 h at 5 °C. Ejaculates were collected from five New Zealand male rabbits by artificial vagina and pooled at 37 °C following evaluation. Each pooled ejaculate was split into three equal experimental groups and diluted to a final concentration of approximately 40 × 10(6)sperm/ml (single step d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 63 publications
7
37
1
Order By: Relevance
“…At the end of 72 h, motility value of BSA5 group was significantly higher than other groups and this motility level (56%) is appropriate for AI. Motility values of liquid stored ram semen ranged between 70% -84%, 60% -80%, 40% -78%, 30% -77% (0, 24, 48 and 72 h, respectively) in previous studies (14,23,24,34). Despite our study performed in non-breeding season, results of our study were in agreement with these values.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…At the end of 72 h, motility value of BSA5 group was significantly higher than other groups and this motility level (56%) is appropriate for AI. Motility values of liquid stored ram semen ranged between 70% -84%, 60% -80%, 40% -78%, 30% -77% (0, 24, 48 and 72 h, respectively) in previous studies (14,23,24,34). Despite our study performed in non-breeding season, results of our study were in agreement with these values.…”
Section: Discussioncontrasting
confidence: 52%
“…It is known that, in addition to antioxidant capacity, BSA accelerates the motility (36,37), protects the membrane (36) and DNA integrity (33), increases the survivability of spermatozoa, and induces the capacitation (40) and acrosome reaction (26). As a consequence of these, BSA supplemented extenders are used for cryopreservation or liquid storage of bull (37), ram (35), goat (6,7), stallion (9), buffalo (2), rabbit (34) and turkey (8) semen.…”
Section: Introductionmentioning
confidence: 99%
“…; Sariozkan et al . ). Glutathione is involved in the protection of male gametes against oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…), buffalo (El‐Kon ) and rabbit (Sarıozkan et al. ). These studies suggested that BSA could improve sperm motility significantly after preservation.…”
Section: Discussionmentioning
confidence: 99%